PENGARUH USIA, PENDIDIKAN, ETNIS, TENURE DAN BOARD OWNERSHIP TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA 2014-2018 - Lidya Eka Putri; Yeasy Darmayanti (Jurnal Kajian Akuntansi dan Auditing, 2021)
Abstract This study aims to prove and analyze the effect of age, education, ethnicity, tenure and board ownership on earnings management in manufacturing companies on the Indonesia Stock Exchange. Sample for the study is manufacturing companies were used which were selected using a purposive sampling method. The data used are from 2014 - 2018. The method of analysis used in this study is multiple regression processed using SPSS. Based on the results of hypothesis testing, it was found that age, education and tenure had influence on earnings management in manufacturing companies on the Indonesia Stock Exchange, while ethnicity and board ownerships had no significant effect on earnings management in manufacturing companies on the Indonesia Stock Exchange Keywords: Age, Education, Ethnicity, Tenure, Board Ownership